2008
DOI: 10.1080/07060661.2008.10540536
|View full text |Cite
|
Sign up to set email alerts
|

Disease progression of Sclerotinia rot of carrot, caused bySclerotinia sclerotiorum, from shoot to root before and after harvest

Abstract: Sclerotinia rot of carrot, caused by Sclerotinia sclerotiorum, is an economically important disease that causes yield loss in stored carrots. To examine the relationship between infection of leaves in the field and disease development in roots, the histopathology of sclerotinia rot within carrot crowns was investigated. Petioles of mature greenhouse-grown carrots were inoculated with mycelium of S. sclerotiorum. Disease progression was monitored in carrots in the greenhouse and in carrots that were harvested a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…They concluded that temperature was not limiting to the disease. However, since then, temperature has been included as one of the variables in forecasting models for Sclerotinia diseases in several crops, including brassicas (Koch et al, 2007;Foster et al, 2008;Clarkson et al, 2014), although other models have excluded temperature and focused on moisture and inoculum levels (Twengstr€ om et al, 1998;Bom & Boland, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that temperature was not limiting to the disease. However, since then, temperature has been included as one of the variables in forecasting models for Sclerotinia diseases in several crops, including brassicas (Koch et al, 2007;Foster et al, 2008;Clarkson et al, 2014), although other models have excluded temperature and focused on moisture and inoculum levels (Twengstr€ om et al, 1998;Bom & Boland, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…severe spoilage. The postharvest soft rot of stored carrot roots is attributed to wellknown pathogens, such as Pectobacterium carotovorum (3)(4)(5), the fungus Sclerotinia sclerotiorum (6)(7)(8), and other microorganisms (9). We recently discovered an additional bacterium, Leuconostoc mesenteroides, responsible for deterioration of stored carrots (10).…”
mentioning
confidence: 99%
“…In carrot, S. sclerotiorum has been reported in over 20 carrot-producing countries and affects both foliage and roots, causing substantial canopy die-back and subsequent crown rot (Jensen et al, 2008). This can also then lead to post-harvest epidemics in storage (Foster et al, 2008). Sclerotinia sclerotiorum also causes lettuce 'drop', where plants quickly wilt in the field due to infection of the stem base and lower leaf axils, followed by rapid rotting of the tissue (Young et al, 2004;Clarkson et al, 2014).…”
Section: Introductionmentioning
confidence: 99%